Introduction to the New Copolymer of Chloroprene and Acrylonitrile with Differentiated Properties - Mousumi De Sarkar; Wataru Nishino; Yuhei Ishigaki; Takashi Sunada (Advances in Polymer Technology)
The random copolymer of chloroprene and acrylonitrile is a newly developed rubber whose features and value propositions are not scientifically explored yet. This article focuses on the basic characterizations and properties of acrylonitrile-chloroprene rubber. Qualitative analyses through infrared (FTIR) and nuclear magnetic resonance (1H-NMR) spectra confirm the presence of both the -Cl and -CN groups in the new rubber. As evidenced through differential scanning calorimetry (DSC) and dynamic mechanical thermal analysis (DMTA), the single glass transition temperature of acrylonitrile-chloroprene rubber reflects its monophasic random microstructure. While compared against commercial grades of chloroprene rubber (CR) and nitrile rubber (NBR), the new rubber provides a distinctive combination of properties that are not available with either of the elastomer alone. Acrylonitrile-chloroprene rubber demonstrates slightly lower specific gravity, an improved low-temperature compression set, higher flex-fatigue resistance, and lower volume swelling in IRM 903 and Fuel C to chloroprene rubber. As compared to nitrile rubber, the new copolymer shows appreciably better heat aging and ozone resistance. Good abrasion resistance, low heat buildup, and remarkably high flex-fatigue resistance indicate excellent durability of the acrylonitrile-chloroprene rubber under dynamic loading. Based on the preliminary results, it is apparent that the new copolymer can be a candidate elastomer for various industrial applications which demand good fluid resistance, high heat and low-temperature tolerances, good weatherability, and durability under static and dynamic conditions.